Relationship between auditory processing skills and academic achievement of elementary school children - Hrastinski, Iva; Bonetti, Ana; Hedjever, Mladen (Specijalna edukacija i rehabilitacija, 2023)
Aim. This study aimed to determine the prevalence of auditory processing difficulties in children and to examine possible relationships between auditory processing skills and school success. Method. In this study, a screening test Auditory processing disorder - (Croatian: PSP – 1) was used to determine the prevalence of auditory processing difficulties in elementary school children in Croatia. Furthermore, correlations between screening test, grade point average, and subjective assessment scores for reading, writing, and math were analyzed. A total of 412 participants from mainstream schools were grouped based on their chronological age and grade. Results. The findings revealed that 12 (approximately 2.9%) participants exhibited difficulties in the assessed auditory processing tasks, which is consistent with data from other studies indicating that between 2% and 5% of children have an auditory processing disorder. Specifically, the two auditory tasks involving dichotic listening proved to be the most challenging for all participants. The results indicated that students’ academic performance, as measured by grade point average and teachers’ ratings of students’ academic and language skills, was poorer in students having pronounced auditory processing difficulties when compared to their same-grade peers. Teacher ratings were significantly correlated with screening test scores, whereas students grade average was not. Conclusions. The analysis also revealed that screening total scores were significantly positively correlated with teachers’ ratings of students’ reading, writing, and mathematical skills. These skills also correlated highly with students’ average grades. These findings corroborate the notion that auditory processing deficits are inversely correlated with academic achievement, warranting further research into the diagnosis and management of Auditory processing difficulties.